1052. Serologic vs. molecular testing for screening for hepatitis C virus infection in patients with hematologic malignancies with and without prior hematopoietic cell transplant recipients. (31st December 2020) - Torres, Harrys A; Angelidakis, Georgios; Jiang, Ying; Economides, Minas; Yibirin, Marcel; MD, Robert Orlowski; Champlin, Richard; Verstovsek, Srdan; Raad, Issam I; Raad, Issam I
Abstract: Background: The prevalence of chronic hepatitis C virus (HCV) infection in patients with cancer in the U.S. has been reported to be 1.5% overall and up to 10.6% in specific subgroups. Testing for antibody to HCV (anti-HCV) is a low-cost diagnostic method in widespread use worldwide; however, the optimal screening test for HCV in cancer patients has not been established. We sought to identify the optimal screening test for HCV in patients with hematologic malignancies and/or prior hematopoietic cell transplant (HCT). Methods: New patients who were seen at the Lymphoma/Myeloma, Leukemia, and Stem Cell Transplant clinics at MD Anderson Cancer Center (02/11/2019-11/5/2019) were simultaneously screened for HCV with serologic (antibody to HCV [anti-HCV]) and molecular (HCV RNA) assays. Anti-HCV testing was performed by using the ARCHITECT Anti-HCV assay and HCV RNA testing was performed by using the Cobas HCV test. The agreement between the two tests was evaluated using Cohen's kappa statistic and McNemar's test. All tests were two-sided with a significance level of 0.05. Results: A total of 214 patients were enrolled in the study, of whom 127 (59%) were men (Table), One hundred forty-nine patients (70%) had a lymphoid neoplasm, 65 (30%) had a myeloid neoplasm, and 15 (7%) underwent HCT. Ninety-three patients (43%) had progressive disease. Three patients (1.4%) had positive anti-HCV, and two (0.9%) had positive HCV RNA. The overall percentage agreement was 99.5% (95% CI, 97.4% to 99.9%). Of the 3 patients with positive anti-HCV, 2 had positive and 1 had negative HCV RNA. There were no cases of seronegative HCV infection. The positive percentage agreement was 66.7% (95 CI, 20.8% to 93.9%), and the negative percentage agreement was 100.0% (95% CI, 98.2% to 100.0%). Cohen's Kappa coefficient was 0·80 (95% CI, 0.41 to 1.00, p < 0·0001), indicating substantial agreement between anti-HCV and HCV RNA tests for diagnosis of HCV infection. Conclusion: The diagnostic yield for screening for chronic HCV infection in heavily immunocompromised cancer patients is similar for serologic and molecular testing. The use of anti-HCV, a diagnostic method with low cost, in patients with cancer would contribute to the World Health Organization's goal of HCV elimination worldwide. Table. Characteristics of the study population (n=214) Disclosures: Harrys A. Torres, MD, Merck & Co., Inc. (Grant/Research Support) Issam I. Raad, MD, Citius (Other Financial or Material Support, Ownership interest)Cook Medical (Grant/Research Support)Inventive Protocol (Other Financial or Material Support, Ownership interest)Novel Anti-Infective Technologies (Shareholder, Other Financial or Material Support, Ownership interest)